An example of the use of Public Health Grid (PHGrid) technology during the 2009 H1N1 influenza pandemic. (8th June 2011) - Boyd, Terry; Lee, Brian; Savel, Thomas; Stinn, John; , Gautam Kesarinath
Historically, public health surveillance systems in the USA have been designed as registries targeting specific public health issues that collect data from certain population groups to answer particular questions. This resulted in disparate public health information systems that can rarely address new needs without extensive redesign. Such a design limits the ability of public health professionals to address emerging public health threats when data need to be collected from different areas of public health practice; the 2009 H1N1 influenza pandemic posed such a challenge. The US Centers for Disease Control and Prevention's Public Health Informatics and Technology Program Office (CDC/PHITPO) and its partners explored a decentralised information architecture using the Public Health Grid (PHGrid). Through the exploration of PHGrid capabilities, CDC/PHITPO developed a pilot project to demonstrate a method for secure and timely data exchange using simulated data in aggregate format.